La transformation des stratégies syndicales en Turquie sous le gouvernement du Parti de la Justice et du Développement (Adalet ve Kalkınma Partisi, AKP) - Isil Erdinç (Cahiers Balkaniques)
In this work, we have addressed the issue of precarity in the labour market in different sectors and its impact on the transformation of trade union strategies. We have highlighted the impact of authoritarian practices and neoliberal policies of the AKP government, in power since 2002.The reforms aimed to increase the competitiveness of certain industries by opening up to international trade. We can conclude in the light of our research that the international economic trade caused the precarization of the labour market in most sectors and has generated the weakening of trade union action, the marginalization of union membership and the criminalization of labour mobilizations.We will focus on three labour union confederations, DİSK, Hak‑İş, Türk‑İş, coming from different political families. Our results are based on a doctoral research conducted since 2011, through ethnographic observations in the unions along with a hundred interviews with union leaders and experts in Istanbul, Ankara, and Sakarya.